2022
DOI: 10.1039/d1fo03062k
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of the first PDZ domain of ZO-1 by glycyrrhizin is a possible mechanism of tight junction opening of Caco-2 cells

Abstract: Glycyrrhizin (GL) is known to exhibit a variety of useful pharmacological activities, including anti-inflammation, anti-hepatotoxicity, and enhancement of intestinal drug absorption. GL has been reported to modify the assembly of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…We previously succeeded in determining the solution structure of mouse ZO-1(PDZ1) using solution NMR experiments found that the C-terminal peptide of CLD-3 and phosphatidylinositol phosphate competitively bound to the canonical peptide binding site of ZO-1(PDZ1) [ 16 ]. In a recent study, ZO-1(PDZ1) was directly inhibited by glycyrrhizin, which prolongs TJ-opening induced by deoxycholate in the Caco-2 cell monolayer [ 33 ]. These results suggest that the direct binding of a small molecule ligand to the CLD binding site of ZO-1(PDZ1) may inhibit the physiologically important interaction between ZO-1(PDZ1) and CLDs, which may result in the malformation of TJ or at least disturb TJ integrity in epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously succeeded in determining the solution structure of mouse ZO-1(PDZ1) using solution NMR experiments found that the C-terminal peptide of CLD-3 and phosphatidylinositol phosphate competitively bound to the canonical peptide binding site of ZO-1(PDZ1) [ 16 ]. In a recent study, ZO-1(PDZ1) was directly inhibited by glycyrrhizin, which prolongs TJ-opening induced by deoxycholate in the Caco-2 cell monolayer [ 33 ]. These results suggest that the direct binding of a small molecule ligand to the CLD binding site of ZO-1(PDZ1) may inhibit the physiologically important interaction between ZO-1(PDZ1) and CLDs, which may result in the malformation of TJ or at least disturb TJ integrity in epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…We previously succeeded in determining the solution structure of mous 1(PDZ1) using solution NMR experiments found that the C-terminal peptide of and phosphatidylinositol phosphate competitively bound to the canonical peptide ing site of ZO-1(PDZ1) [16]. In a recent study, ZO-1(PDZ1) was directly inhibi glycyrrhizin, which prolongs TJ-opening induced by deoxycholate in the Caco-2 cel olayer [33]. These results suggest that the direct binding of a small molecule ligand…”
Section: Nmr Evidence Of Direct Binding Of Hst But Not Que To Zo-1(pdz1)mentioning
confidence: 99%
“…Sodium deoxycholate can open the TJs of the Caco-2 monolayer model, activate the paracellular pathway, reduce the TEER value, and increase the amount of the hydrophilic substance in the paracellular pathway; therefore, we selected sodium deoxycholate as the paracellular absorption promoter. The tolerance concentrations of QMDDQ and sodium deoxycholate in Caco-2 cells were determined by the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…Liang et al used a Caco-2 cell model to study the effects of total coumarins and volatile oils in radix Angelica dahurica on cell permeability by inhibiting the expression of ZO-1 and actin and opening TJs. Hibino et al used NMR experiments and Haddock construction to study the combination of glycyrrhizin and the first PDZ domain of ZO-1 (ZO-1 (PDZ1)), which directly inhibits the expression of ZO-1, regulates the integrity of TJs, and enhances absorption. Claudin-2 is an important selective pore-forming TJ protein in the intestinal epithelium, which can form small cations and water paracellular channels; the expression of claudin-2 was contrary to that of ZO-1 and occludin.…”
Section: Resultsmentioning
confidence: 99%